The definition of a public official in criminal law - Pariona Arana, Raúl Belealdo (2024)
This article addresses the concept of a public official in criminal law, the content and scope of which constitutes one of the central topics of contemporary legislation. Modern criminal doctrine has developed an autonomous penal concept of public official, which is not limited to the parameters of labor administrative law and has been reflected in Article 425 of the Penal Code in Peru. Two central components define the concept of a public official for criminal purposes: the enabling title for incorporation into the public administration and the exercise of public office. From this doctrinal perspective, the article discusses the issue of determining the moment at which the status of public official is acquired in cases of officials elected by popular vote. Finally, this research details the problematic nature of the “de facto public official,” supporting the illegitimacy of the concept due to the lack of legal backing and distinguishing it from the case of usurpation of functions. The situation is different for public officials with irregular titles.